A Review on the Effect of Online Learning Environment and Teachers and students of primary school - Kairon Mubina M.S. (AG Volumes, 2022)
The use of the internet to get schooling is now both innovative and common. Every day, there is more money being made in the online education and e-learning industries. Many individuals have found that participating in online education may be an efficient method to further their education or that it can open doors to new career prospects. When online education first became available, it presented a number of challenges for both students and educators. Kids' academic performance has suffered significantly as a direct result of the epidemic, which has also had a negative impact on their studies. Kids began spending a lot of time on their cell phones. During their time spent studying online, students in primary school have encountered a great deal of difficulty. Getting an education via an online platform, particularly when you're just starting out, may be a challenging experience. We are all aware that children in elementary schools require a greater amount of attention than other students, and it is a challenging task for teachers to oversee their students' activities in an online learning environment because they must be physically separated from their pupils and are unable to observe their behaviour directly. The COVID-19 pandemic results in widespread use of online learning environments, which has fundamentally altered the educational landscape. Even when the negative effects of Covid-19 have been mitigated, online education will continue.The education of elementary school children is the basis, and it is very necessary that the foundation, also known as the base, be robust. Teachers and students in an online learning environment don't have too many opportunities to engage with one another, and they also can't physically meet with one another. It is essential for a child who is prepared to start school to have social interactions with persons other than his or her family members and to get together with other children in order for them to be able to learn many things that are not related to their academic pursuits.